Importance of a timely diagnosis of oral squamous cell carcinoma. A case report and review of the literature - Larreta Gutiérrez, Andrés Gabriel (2020)
The relevance of a timely diagnosis in oral cavity cancer is pointed out, as well as a brief synthesis of the literature. The case of a female patient who attends the UNAM Oral and Maxillofacial Surgery Clinic with a history of having undergone several biopsies in which no conclusive results were found, is reported. Therefore, it was decided to perform an incisional biopsy in order to define the pathology. The article aims to emphasize the importance of a correct and timely diagnosis, so that the patient can receive the best treatment. In conclusion, the role played by the specialist in an early and accurate detection and the overall commitment of the patient can considerably reduce morbidity and mortality.